2008
DOI: 10.1080/13880200802055917
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Composition ofCymbopogon winterianus. andCarum carvi. and Their Antimicrobial Activities

Abstract: The chemical composition and antimicrobial activity of Cymbopogon winterianus Jowitt (syn. Cymbopogon nardus (L.) W. Watson var. mahapengiri Winter) (Poaceae) and Carum carvi L. (Apiaceae) essential oils were investigated against 19 fungal and 7 bacterial species. Among the tested species were food contaminants, spoilage fungi, as well as plant or fungi and animal pathogens. In order to determine minimal inhibitory concentrations (MICs) minimal fungicidal concentrations (MFCs) and minimal bactericidal concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 15 publications
7
72
2
4
Order By: Relevance
“…Some fungitoxic substances were already identified in mentrasto Esper et al, 2014), rue (Domingues et al, 2009;Azizi & Karouei, 2012), ginger (Sharma & Tiwari, 2013), false saffron (Ferreira et al, 2013;Parveen et al, 2013), citronella (Simic et al, 2008), rosemary (Ozcan & Chalchat, 2008), neem (Coventry & Allan, 2001) and eucalyptus citriodora (Aguiar et al, 2014). It is likely that fungicidal substances of wide spectrum present in the extracts and essential oils of these plants are involved in the inhibition of S. cepivora, such as precoceno in mentrasto , citronellal in citronella and eucalyptus citriodora (Simic et al, 2008;Tomazi et al, 2014), 1.8-cineole (eucalyptol) in ginger and rosemary (Ozcan & Chalchat, 2008;Sharma & Tiwari, 2013) and azadirachtin in neem (Coventry & Allan, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Some fungitoxic substances were already identified in mentrasto Esper et al, 2014), rue (Domingues et al, 2009;Azizi & Karouei, 2012), ginger (Sharma & Tiwari, 2013), false saffron (Ferreira et al, 2013;Parveen et al, 2013), citronella (Simic et al, 2008), rosemary (Ozcan & Chalchat, 2008), neem (Coventry & Allan, 2001) and eucalyptus citriodora (Aguiar et al, 2014). It is likely that fungicidal substances of wide spectrum present in the extracts and essential oils of these plants are involved in the inhibition of S. cepivora, such as precoceno in mentrasto , citronellal in citronella and eucalyptus citriodora (Simic et al, 2008;Tomazi et al, 2014), 1.8-cineole (eucalyptol) in ginger and rosemary (Ozcan & Chalchat, 2008;Sharma & Tiwari, 2013) and azadirachtin in neem (Coventry & Allan, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The other important compounds extracted usually from hydro/steam distillation include: carvacrol, a-pinene, g-terpinene, linalool, carvenone, and p-cymene. [14][15][16] The fruits of caraway are used extensively as a mild spice and flavoring for culinary purposes in many cuisines. The dried, brown fruits are hard, crescent-shaped achenes, around 2 mm long with five pale ridges.…”
Section: Other Fruits Of Apiaceae Familymentioning
confidence: 99%
“…This species is known for its pharmacological properties such as antimicrobial, antiinflammatory, antioxidant and mosquitocidal (Nurhanani & Othman, 2010;Silva et al, 2011;Kongkaew et al, 2011;Sritabutra et al, 2011;Istianto & Emilda, 2011;Simic et al, 2008). Nakahara et al (2003) reported that the main constituents of C. nardus are geraniol, trans-citral, cis-citral, geranyl acetate, cintronellal and citronellol.…”
Section: Introductionmentioning
confidence: 99%